Levels of well-being according to demographic variables in Saudi Arabia: a PERMA model survey study - Almeqren, Monira A.; Alsukah, Aljawharh; Almuqrin, Aljawharah; Alzeiby, Ebtesam A.; Alamri, Ali F.; Alshebali, Munirah; AlGadheeb, Nourah A. (Frontiers in Psychology, 2025)
ObjectiveThis study aims to assess the level of well-being among the Saudi population based on their demographic variables.MethodsThe sample comprised 2,927 individuals from 13 regions of the Kingdom, selected through a stratified random sampling method. The study utilized the PERMA model of well-being as its primary tool. The findings revealed that the participants’ average scores on the well-being scale ranged from 5.035 to 7.879, with an overall arithmetic mean of 6.569, indicating a high level of well-being.ResultsThe results showed no significant gender-based disparities in well-being levels. However, variations were observed across different educational levels. The study also found consistently high levels of well-being across all sub-categories of nationality, income, and family size.ConclusionThe researcher recommends that officials in Saudi Arabia continue their efforts to enhance the psychological well-being of individuals by implementing diverse activities and programs aimed at promoting psychological safety and improving overall well-being.